Indonesia : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report, 2008)
Indonesia' 2008 Article IV Consultation reports that Indonesia's growth performance remains strong despite the deteriorating global environment. The economy remains vulnerable to shifts in investor sentiment, and volatility in the government bond market has increased. The new policy of increased reselling of official foreign exchange receipts from oil exports should support the rupiah and help dampen inflation, but a more automatic mechanism for recycling official reserves would, in addition, enhance liquidity and foreign exchange market development.